[Munājāt ʻAlī ... etc., 994, i.e. 1585 or 1586]. - ʻAlī ibn Abī Ṭālib; Sadeddin, Hoca; Mehmet Rıza (قصيدة عينية, 1585)
Elegant copy of a majmūʻah with the qaṣīdah in ʻayn, Munājāt ʻAlī, from the dīwān attributed to ʻAlī ibn Abī Ṭālib (ca. 600-661), followed by a collection of seal impressions (decoratively mounted) and a later assortement of excerpts in verse and prose, in Persian and Turkish. Contribution to the cataloguing from Ali Rafi.
Shelfmark: Ann Arbor, University of Michigan, Special Collections Research Center, Isl. Ms. 437
Origin: As appears in colophon at close of on fol.4a, Munājāt ʻAlī executed in Istanbul for Hoca Sadettin Efendi (d.1599), renowned şeyhülislâm and tutor of Sultan Murat III (r.1574-1595), by Mehmet Rıza, Rıza-yi Enesi [of Enez in Edirne?]. Poetic excerpts appear to be dated Dhū al-Ḥijjah 1138 [July-August 1726] (see fol.12b, fol.22a, etc.) and 15 Muḥarram 1139 [ca. 12 September 1726] (see fol.1a).
Former shelfmark: "198 T. De M. [i.e. Tammaro De Marinis]" inscribed in pencil on verso of opening leaf ('title page').
Binding: Pasteboards covered in black leather ; Type III binding (without flap) ; doublures in brown leather, doublure hinges (extending under doublures) in scalloped marbled paper (in blue and white) ; upper and lower covers carry gold-tooled ornament (octagonal or lobed diamond shape) built up from interlace pattern, along with tooled and gold-painted border in a series of s-shaped stamps ; sewn in white thread, four stations ; overall in fairly good condition with minor staining, etc. ; repair to spine (rebacked) in black leather (gone to gray).
Support: non-European laid paper with roughly 8 laid lines per cm. (vertical, somewhat indistinct) and occasional chain lines faintly visible, cloudy formation, thick and sturdy, well-burnished ; "leaves" mainly composed of two (occasionally more) leaves layered together, delaminating in several instances, with several now hinged together / guarded with strips of striped textile ; some leaves tinted (mainly yellow) and gold or silver flecked ; seal impressions mounted on decorative papers.
Keywords: Manuscripts, Turkish / Michigan / Ann Arbor.; Manuscripts, Persian / Michigan / Ann Arbor.; Manuscripts, Arabic / Michigan / Ann Arbor.; Stamp seals / Middle East.; Stamp seals / Turkey.; Writing, Arabic / Specimens.; Calligraphy, Persian / Specimens.; Calligraphy, Arabic / Specimens.; Islam / Prayers and devotions / Early works to 1800; Arabic poetry / 622-750 / http://id.loc.gov/authorities/subjects/sh85006335